Sobre o completamento I-ádico e a teoria de homologia local para módulos Artinianos - Nascimento Filho, Antonival Lopes do (2016)
In this work we study the I-adic completion functor, its properties and main results. Moreover, we study local homology modules as de ned by N. T. Cuong and T. T. Nam. The nal part of this work is reserved to the study of local homology of Artinian modules. In some aspects, local homology theory has a dual behaviour with respect to Grothendieck's local cohomology theory of sheaves.